A RARE CAUSE OF BOTH HYPO AND HYPERGLYCEMIA; GLYCOGEN STORAGE DISEASE TYPE 0: A CASE REPORT - Meryem Karaca; Halil Aslan (İstanbul Tıp Fakültesi Dergisi)
Glycogen-storage disease type 0A is a rare autosomal recessively inherited disease resulting from a hepatic glycogen synthase enzyme deficiency. Glycogen-storage disease type 0A is characterized by fasting ketotic hypoglycaemia, postprandial hyperglycemia and lactic acidemia without hepatomegaly. In clinical practice, patients may be asymptomatic, or may present with hypoglycemic convulsions, short stature, growth retardation, osteopenia, and rarely symptoms of hyperglycemia. In this article, we present a 6-year-old girl with previous symptoms of hypoglycaemia, and symptoms of hyperglycemia at the time of admission and genetically diagnosed as glycogen storage disease type 0A.